Incidence of Hand-Foot Syndrome in Metastatic Breast Cancer Patients Treated with Capecitabine in Middle Euphrates Region of Iraq - Mjali, Ahmed; Hasan, Zahraa Kadhim (Scientific Journal of Medical Research, 2020)
Background: Capecitabine is a fluoropyrimidine which is converted to 5-fluorouracil (5-FU) at the tumor site. Objectives: To evaluate the incidence of hand-foot syndrome (HFS) in metastatic breast cancer patients treated with capecitabine in our region. Methods: A retrospective descriptive study conducted at Al- Hussein cancer center in Karbala province of Iraq between April 2018 and August 2020.There were 58 female patients with metastatic breast cancer treated with capecitabine as monotherapy included in our study. Results: About 77.59% of our patients developed HFS , patients > 40 years old were the most affected age group in 84.44%. Majority of our patients were grade 1 in 66.67% and more than half patients (51.11%) developed their first episode of HFS after third cycle. Conclusion: Capecitabine is a well-tolerated treatment with low toxicity, most of our patients presented in early grades and first symptoms tend to occur after third cycle.